Annual review of comparative and international education 2021. volume 42, part A - Wiseman, Alexander W. (International perspectives on education and society ;, 2022)
Since 2013, the Annual Review of Comparative and International Education has covered significant developments in the intersecting fields of comparative education, international education, and comparative and international education. The Annual Review of Comparative and International Education 2021, Part A, begins with a collection of discussion essays about comparative and international education trends and directions, followed by studies that focus on new developments in comparative and international education by regional area. Topics covered in this volume include diversity in research trends in comparative and international education; refugee education programs; the syndemic of race, gender, and Covid-19; the impact of Covid-19 in schools; the right to education in South American countries; the effects and challenges of online learning during the pandemic in China; and a comparison of racial and ethnic inequalities in South Africa. With contributions from leading scholars and professionals across the field of comparative and international education, this edition will be of use to education researchers and professionals alike.